2017
DOI: 10.3389/feart.2016.00109
|View full text |Cite
|
Sign up to set email alerts
|

On the Coherence in the Boundary Layer: Development of a Canopy Interface Model

Abstract: A 1D Canopy Interface Model (CIM) is developed to act as an interface between a meso-scale and a micro-scale atmospheric model and to better resolve the surface turbulent fluxes in the urban canopy layer. A new discretisation is proposed to solve the TKE equation finding solutions that remain fully concordant with the surface layer theories developed for neutral flows over flat surfaces. A correction is added in the buoyancy term of the TKE equation to improve consistency with the Monin-Obukhov surface layer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 45 publications
(49 reference statements)
2
30
0
Order By: Relevance
“…As 70% of the world's population is expected to live in urban areas by 2050 (United Nations, 2014), it is critical to better understand and represent these issues. To do so, urban canopy models (UCM) were developed with the perspective of giving quantitative decision support for the mitigation of, and adaptation to, climate change through urban planning and policymaking (Masson, 2000;Kusaka et al, 2001;Martilli, 2002;Järvi et al, 2011;Mauree et al, 2017). However, a major impediment to the use of UCMs is the lack of data on urban morphologies and related local weather data, which is crucial for the implementation and testing of such models (Oke, 2006;Grimmond et al, 2010;Grimmond et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As 70% of the world's population is expected to live in urban areas by 2050 (United Nations, 2014), it is critical to better understand and represent these issues. To do so, urban canopy models (UCM) were developed with the perspective of giving quantitative decision support for the mitigation of, and adaptation to, climate change through urban planning and policymaking (Masson, 2000;Kusaka et al, 2001;Martilli, 2002;Järvi et al, 2011;Mauree et al, 2017). However, a major impediment to the use of UCMs is the lack of data on urban morphologies and related local weather data, which is crucial for the implementation and testing of such models (Oke, 2006;Grimmond et al, 2010;Grimmond et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These models require significant computational resources and are not practical for the evaluation of urban planning scenarios which thus becomes a tedious task. Mauree et al, [38,39] have therefore developed an urban canopy model, CIM to provide high-resolution vertical profiles to building energy models. In a previous study, they validated the coupling of CIM with CitySim and demonstrated the advantage of the coupling in the simulation of building energy use in an urban district [4].…”
Section: Urban Simulation Workflows For Climate Changementioning
confidence: 99%
“…CIM is an urban canopy model that can be used in an offline mode to provide high resolution data for building energy simulation tools [39]. It has already been coupled with CitySim to take into account the particularities of urban areas, to improve building energy simulations [4].…”
Section: Cimmentioning
confidence: 99%
See 1 more Smart Citation
“…The BUBBLE Sperrstrasse site was chosen here for three primary reasons: (1) the site provided a continuous dataset of radiation and meteorological variables over the course of nearly one year for a representative mid-latitude city. This allowed for examination of urban T surf the surface urban heat island effect (sUHI), and atmospheric correction magnitudes over a wide range of representative mid-latitude conditions; (2) inclusion of T facet over the IOP allows for investigation of the effect of sensor FOV and viewing direction on remote sensed urban T surf for common methods of urban T surf retrieval; and (3) the site has been used in multiple validation exercises for urban climate models [21,22].…”
Section: Study Areamentioning
confidence: 99%